Maternal Knowledge Regarding Stunting in Toddlers: An Overview - Novianti, Donna; Setiawan, Henri; Sukmawati, Ima (Inspirasi Foundation, 2024)
Introduction: Stunting is a significant public health issue that affects the growth and development of children, particularly in their early years. One of the key factors contributing to stunting is the level of knowledge that mothers of toddlers have regarding proper nutrition and child care. Understanding the awareness and knowledge of mothers about stunting is crucial in developing effective interventions and educational programs to prevent its occurrence. This study aims to examine the level of maternal knowledge about stunting and its potential impact on the health and development of toddlers. Objective: The objective of this study is to assess the level of knowledge among mothers of toddlers regarding stunting and its contributing factors. Methods: This study employed a cross-sectional design to assess the level of knowledge among mothers of toddlers regarding stunting. The population of the study consisted of mothers with toddlers in Mulyajaya, Sumedang Regency. A total of 18 mothers were selected as the sample using a total sampling technique. Data collection took place between February 14 and May 14, 2024. The collected data were analyzed using frequency and percentage calculations, with statistical analysis performed using SPSS version 22. This approach allowed for a comprehensive understanding of the knowledge level regarding stunting among the participants. Results: The results of this study show that in the group of mothers with toddlers, the number of respondents with an improved level of knowledge was observed. Conclusions: The majority of mothers with toddlers in Mulyajaya have sufficient knowledge about stunting, with some demonstrating good knowledge. However, a small group still lacks adequate understanding. This highlights the need for targeted educational interventions to improve maternal knowledge and promote better child care practices.